2018
DOI: 10.1098/rsbl.2018.0051
|View full text |Cite
|
Sign up to set email alerts
|

Role of the light source position in freely falling hoverflies' stabilization performances

Abstract: The stabilization of plummeting hoverflies was filmed and analysed in terms of their wingbeat initiation times as well as the crash and stabilization rates. The flies experienced near-weightlessness for a period of time that depended on their ability to counteract the free fall by triggering their wingbeats. In this paradigm, hoverflies' flight stabilization strategies were investigated here for the first time under two different positions of the light source (overhead and bottom lighting). The crash rates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In line with previous studies carried out at our laboratory (Goulard et al, 2015(Goulard et al, , 2016(Goulard et al, , 2018a, hoverflies were dropped under free-fall conditions, upside-down with their legs touching the top of the box, in order to study aerial righting in flies for the first time. As expected, hoverflies in the upside-down position were found to trigger their wingbeats and to rotate quickly in order to regain the right-side up position within a short lapse of time (48.8 ms; see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous studies carried out at our laboratory (Goulard et al, 2015(Goulard et al, , 2016(Goulard et al, , 2018a, hoverflies were dropped under free-fall conditions, upside-down with their legs touching the top of the box, in order to study aerial righting in flies for the first time. As expected, hoverflies in the upside-down position were found to trigger their wingbeats and to rotate quickly in order to regain the right-side up position within a short lapse of time (48.8 ms; see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The DLR is a reflex that several families of insects use to determine their orientation based on the fact that the brightest part of the environment is presumably located above them (Mittelstaedt, 1950;Hengstenberg, 1993;Goulard et al, 2015Goulard et al, , 2018aMeyer and Bullock, 1977;Schuppe and Hengstenberg, 1993). In a previous experiment, Goulard et al (2018a) showed that lighting from below drastically affects hoverfly stabilization during free fall, which proves that hoverflies are highly sensitive to light coming from the ground. In the present case, the halogen light projected from below would provide the hoverfly (upside-down) with a vertical reference frame oriented in the appropriate position.…”
Section: Proprioceptive Processes Used To Detect the Upside-down Statementioning
confidence: 99%
“…There is an indication that something like this might be happening in day-flying hover flies, Episyrphus balteatus. A recent study shows that altering the position of the dominant light source affects the ability of hover flies to stabilize their flight (Goulard et al, 2018). In this case, the authors suggest that input from the dorsal part of the eyes is the sensory information needed for the animal to orient dorsal side up and ventral side down.…”
Section: Plume Tracking and Optomotor Behaviors Unaffected By Lack Ofmentioning
confidence: 99%
“…The flies had prior knowledge of their orientation with respect to gravity, as they were always in contact with the ceiling before being released ( P ). As a fly deprived of proprioception before being released crashes irremediably onto the ground 16 , 30 , we did not include any condition without proprioception. Sensory conflicts were introduced by varying the visual inputs (lighting from above or below) and the state of the antennae (glued or intact).…”
Section: Resultsmentioning
confidence: 99%